Alcohol consumption and cognitive impairment among Chinese older adults: 8‐year follow‐up of Chinese Longitudinal Healthy Longevity Study. (31st December 2021) - Zhao, Ziyi; Li, Bingyu; Wei, Chang; Sha, Feng
Abstract: Background: This is the first study examining the association between alcohol consumption and risk of cognitive impairment (CI) among Chinese older adults (65‐79 years). Method: The study included 5, 894 participants between 65 and 79 years from 2002‐2008 Chinese Longitudinal Healthy Longevity Study (CLHLS). The CI was assessed by Chinese version of Mini‐Mental State Examination (MMSE) . The self‐reported alcohol type and consumption were assessed and converted into pure alcohol consumption in gram. The adjusted cox proportional hazard model was implemented with age as time scale. With abstainers as the reference, hazard ratio (HR) for cognitive impairment was calculated for five levels of alcohol consumption (former drinker, 0.1‐175.0 g for male/0.1‐105.0 g for female per week, 175.1‐350.0 g for male/105.1‐210.0g for female per week, 350.1‐525.0 g for male/210.1‐315.0 g per week, >525.0 g for male/>315.0 g for female per week). Result: 837 (14.2%) participants developed CI in the follow‐up waves with mean follow‐up of 7.9 (SD 4.6, range 0.17‐17.3) years. There was no evidence that low‐to‐moderate alcohol consumption (0.1‐175.0 g for male/0.1‐105.0 g for female per week) was associated with increased risk of CI (HR: 1.25, 95% CI: 0.91‐1.74); however, heavy alcohol use (>525.0 g for male/>315.0 g for female per week) was associated with increased risk of CI (HR: 1.37, 95% CI: 1.01‐1.84). Compared with abstainers, former drinkers had higher risk of cognitive impairment (HR: 1.50, 95% CI: 1.17‐1.92). In addition, among former drinkers, previous consumption of alcohol above 175.0 g/week for male and 105.0 g/week for female was associated with higher incidence of dementia (HR: 1.61, 95% CI: 1.22‐2.11). Conclusion: Excess alcohol consumption in men (>525.0 g/week) and in women (>315.0 g/week) are both significantly associated with increased risk of CI. There is no evidence that low‐to‐moderate alcohol drinking had protective effect against CI. Among former drinkers, heavy drinkers have higher risk of CI compared to non‐drinkers, suggesting heavy consumption of alcohol negatively influences one's cognitive health in later life even after abstinence. Further investigation is required to determine whether these relationships are mediated by specific environmental or genetic factors.